Evaluating Financial Performance of SBI Through Financial Ratios - Maheshwari, Neeta; Agarwal, Neha (Indian Journal of Finance, 2013)
The objective of the present paper is to analyze the financial performance of SBI (State Bank of India) over a period of eleven years (2002-2012). For this purpose, financial ratio analysis has been used. With the help of this analysis, it was inferred that in the public sector banks, SBI is the top ranking bank in India, with its performance in terms of financial soundness being the best. For this analysis, investment valuation ratio, profitability ratio, management efficiency ratio, balance sheet ratio, and cash flow indicators were used. Results indicate that the performance of SBI in the study period has been excellent. SBI’s excellent performance can be attributed to the adoption of modern technology, banking reforms, and good recovery mechanisms. However, SBI needs to improve its position with regards to a few parameters including debt-equity, operating profit, and non-interest income to total income.